Development of molecular oncohematology in Ukraine - Telegeev, G.D.; Dybkov, M.V.; Dubrovska, A.N.; Miroshnichenko, D.A.; Tyutyunnykova, A.P.; Maliuta, S.S. (Вiopolymers and Cell, 2013)
Disruption of the genetic component of cells are mandatory element of malignant transformation. For the majority of blood neoplasias genetic disorders have been discovered, and they can be used for diagnosis and appropriate therapy. The data obtained by authors about the role of domains of Bcr-Abl protein (the main etiological factor in the pathogenesis of leukemia with Ph-chromosome) are presented in this review as well as approved diagnostic methods for myeloproliferative disorders and acute leukemias.